Cycling as the best sub-8-hour performance predictor in full distance triathlon - Sousa, C. V.; Pinheiro Barbosa, L.; Magalhães Sales, M.; Santos, P. A.; Tiozzo, E.; Simões, H. G.; Nikolaidis, P. T.; Knechtle, B. (Sports, 2019)
For any triathlon distance (short, Olympic, half-distance and full-distance), competitors spend more time cycling than swimming or running, but running has emerged as the discipline with the greatest influence on overall performance at the Olympic distance. However, there is a lack of evidence on which discipline has the greatest influence on performance in the overall full-distance triathlon (3.8 km swimming/180 km cycling/42.195 km running), especially for the fastest performing athletes of all time. The total race times of 51 fastest triathletes (sub-8-hour) were studied, while for the split times, a sample of 44 participants was considered. The discipline that seemed to better predict total race time was cycling (coefficient = 0.828; p < 0.001), followed by running (coefficient = 0.726; p < 0.001) and swimming (coefficient = 0.476; p < 0.001). Furthermore, cycling was the discipline with the highest performance improvement over the years, whereas running had a slightly decrease. In conclusion, cycling seems to be the discipline with greater influence in final result for the full-distance triathlon